Dampak Konseling Keluarga terhadap Kesejahteraan Emosional Anggota Keluarga (Studi Kasus) - Hidayani Syam; Elfina Awlia Ramadani; Misna Misna; Alya Wiri Agnesia (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Family counseling is a form of psychological intervention designed to help family members resolve interpersonal conflicts, improve communication, and build healthier relationships. This study aims to examine the impact of family counseling on the emotional well-being of family members. Through a qualitative approach and literature review, it was found that family counseling contributes greatly to reducing stress levels, increasing empathy, improving communication patterns, and strengthening emotional bonds between family members. These findings confirm the importance of family counseling as a strategic means in improving the quality of individual emotional life in the family system.